Large Spectral Shift of Reflected Radiation From Laser Plasmas Generated by High Contrast KrF Laser Pulses - Kovács, Zsolt; Gilicze, Barnabás; Szatmári, Sándor; Földes, István B. (Frontiers in Physics, 2020)
Strong absorption increasing with intensity was observed in boron and gold laser plasmas heated by KrF laser pulses of high, but still nonrelativistic intensity. The pulses of 700 fs duration had a temporal contrast of 12 orders of magnitude, thus the laser pulse of >10^18 W/cm^2 intensity hit the steep surface of the boron and gold targets. Blue shift of the reflected radiation refers to extreme high acceleration resulting in velocities above 5*10^7 cm/s. Brunel absorption and ponderomotive effects are shown to play important role in the observed phenomena.